2019
DOI: 10.1242/jeb.204669
|View full text |Cite
|
Sign up to set email alerts
|

Not that hot after all: no limits to heat dissipation in lactating mice selected for high or low BMR

Abstract: Heat dissipation has been suggested as a limit to sustained metabolic effort, e.g. during lactation, when overheating is a possible risk. We tested this hypothesis using mice artificially selected for either high or low BMR that also differed with respect to parental effort. We used fixed size cross-fostered families and recorded litter mass daily until the 14th day of lactation. Midway through the experiment (day 8) half of the mothers from each group had fur from the dorsal body surface removed to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…In the present study, food intake, digestive energy intake, milk energy output or litter mass did not differ between F1 female adults that previously weaned at 32.5 and 21°C when they were lactating at 21°C. Consistent with these data, Swiss mice artificially selected for either high or low basal metabolic rate, which had had fur from the dorsal body surface removed to increase their thermal conductance and facilitate heat dissipation, did not benefit from increasing their thermal conductance at peak lactation (Sadowska et al, 2019). This is also consistent with previous data which indicate at 21°C that this strain is probably not limited by the capacity for heat dissipation (Wen et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, food intake, digestive energy intake, milk energy output or litter mass did not differ between F1 female adults that previously weaned at 32.5 and 21°C when they were lactating at 21°C. Consistent with these data, Swiss mice artificially selected for either high or low basal metabolic rate, which had had fur from the dorsal body surface removed to increase their thermal conductance and facilitate heat dissipation, did not benefit from increasing their thermal conductance at peak lactation (Sadowska et al, 2019). This is also consistent with previous data which indicate at 21°C that this strain is probably not limited by the capacity for heat dissipation (Wen et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Nestling‐feeding blue tits ( Cyanistes caeruleus ) with removed ventral plumage sired larger nestlings, maintained lower temperature and lost less body mass (Nord, Nilsson, & Portugal, 2018). However, other studies on reproducing mammals did not support HDL predictions (Zhao, Chi, & Cao, 2010; Sadowska et al ., 2019), thus casting doubt on its generality. Furthermore, reproducing mammals or birds do not lose fur or feathers, which is likely because of the risk of death if the temperature suddenly drops, which would on average decrease their lifetime reproductive success.…”
Section: Mechanistic Explanation Of Hypoallometric Mr Scalingmentioning
confidence: 99%
“…Explanations of the limits on female lactation performance are disputed. The 'central limitation' hypothesis suggests that the limits are imposed by the uptake capacity of the energy-supplying machinery (such as the alimentary tract and associated organs) (Perrigo, 1987;Diamond, 1992, 1994;Koteja, 1996;Thurber et al, 2019;Sadowska et al, 2019). More recent evidence in small mammals tends to support the 'peripheral limitation' or 'heat dissipation limitation' (HDL) theories.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, surgically removing half of the mammary glands in Swiss mice had an impact on pup growth (Hammond et al, 1996), which also supports the idea that the mammary gland imposes the limit on milk production capacity at room temperature in this strain. Another study in artificially selected Swiss mice (high and low basal metabolic rate lines) showed that the lactation performance of both lines did not benefit from increasing their thermal conductance at peak lactation by fur removal (Sadowska et al, 2019). This also suggested that the limit was not imposed by heat dissipation capacity, but rather by the spare capacity of the alimentary tract and other organs to respond to such sudden energy demand (Sadowska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%